2021
DOI: 10.1136/jitc-2021-002841
|View full text |Cite
|
Sign up to set email alerts
|

CD11b+CTLA4+myeloid cells are a key driver of tumor evasion in colorectal cancer

Abstract: BackgroundTumor metastasis is the major cause of death of colorectal cancer (CRC), and metastatic CRC remains incurable in many cases despite great advances in genetic and molecular profiling, and clinical development of numerous drugs, including immune checkpoint inhibitors. Thus, more effective treatments are urgently needed for the patients in clinical settings.MethodsWe used mouse CRC metastasis models that murine Colon26 cells were subcutaneously and intravenously implanted and attempted to elucidate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…These findings indicate that CTLA-4 may regulate the induction and functional state of MDSCs and macrophages [ 69 ]. In accordance, it has been observed that CD11b + CTLA-4 + cells mediated tumor progression via IL-1β production and by CTLA-4 signaling in a mouse model of CRC [ 70 ]. More specifically, Yang and coworkers reported that MDSC-mediated immunosuppression in a murine model of ovarian cancer was significantly reduced upon CTLA-4 blockade, which was largely attributed to a reduction in arginase I activity by these cells [ 71 ].…”
Section: Treatment Of Metastatic Melanoma and Other Solid Tumors With...supporting
confidence: 52%
“…These findings indicate that CTLA-4 may regulate the induction and functional state of MDSCs and macrophages [ 69 ]. In accordance, it has been observed that CD11b + CTLA-4 + cells mediated tumor progression via IL-1β production and by CTLA-4 signaling in a mouse model of CRC [ 70 ]. More specifically, Yang and coworkers reported that MDSC-mediated immunosuppression in a murine model of ovarian cancer was significantly reduced upon CTLA-4 blockade, which was largely attributed to a reduction in arginase I activity by these cells [ 71 ].…”
Section: Treatment Of Metastatic Melanoma and Other Solid Tumors With...supporting
confidence: 52%
“…MDSCs are pathologically activated myeloid progenitors and immature myeloid cells with potent immunosuppressive activity ( Hegde et al, 2021 ; Veglia et al, 2021 ). A number of studies have demonstrated that MDSCs are implicated in T cell suppression and are closely associated with poor clinical outcomes in cancer ( Wang et al, 2020b ; Imazeki et al, 2021 ). Mouse experiment also demonstrated that MDSC depletion with antibodies or different compounds could substantially improve anti-tumor immune responses to exert anti-tumor effects ( Gabrilovich et al, 2012 ).…”
Section: Vaccines Targeting P53mentioning
confidence: 99%
“…CYBA can induce familial colorectal cancer by interfering with the integrity of intestinal barrier [ 36 ]. IL-1B, as a member of the interleukin family, is closely related to tumor immunity [ 37 ]. SOD2 contributes to the chemical resistance of colorectal cancer [ 38 ], and according to research, MAPK8 can promote the progression of colorectal cancer [ 39 ].…”
Section: Discussionmentioning
confidence: 99%